The impact of EU public procurement regulations on tenders in Spain: a study with adalimumab - Esplugues, F. J.; Andújar, I.; Esplugues, J. V. (Frontiers in Pharmacology, 2024)
Pharmaceutical spending accounts for a significant portion of public healthcare budgets. To manage these costs, EU countries implement various cost-containment policies, including competitive tendering for pharmaceuticals. This study examines the impact of EU public procurement regulations on medication procurement practices, specifically focusing on adalimumab tenders in Spain from 2018 to 2024, a period that coincides with the implementation of European legislation and the emergence of adalimumab biosimilars. Our findings reveal substantial price reductions following the introduction of adalimumab biosimilars, yet highlight significant variability in tender criteria and practices across different regions. Despite adherence to EU directives, the inconsistent application of economic and non-economic factors and an erratic criteria concerning price undermine the intended balance of quality and cost, complicating procurement processes and potentially affecting the availability of a given treatment for patients.